2022
DOI: 10.2166/ws.2022.108
|View full text |Cite
|
Sign up to set email alerts
|

The concentration and prevalence of asbestos fibres in Christchurch, New Zealand's drinking water supply

Abstract: Asbestos cement was a common construction material for water pipes during the twentieth century, as a replacement for metal piping that was vulnerable to corrosion. We report on the presence of asbestos fibres in drinking water supply in Christchurch, New Zealand from aging asbestos cement reticulated water supply. By sampling the mains water supply via hydrants, 19 of our 20 samples showed long asbestos fibres (>10 μm), with an average concentration 0.9 million fibres per litre (MFL). Short asbestos fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A study conducted in Christchurch, New Zealand [ 64 ], reported on the presence of asbestos fibers in the drinking water supply due to aging asbestos-cement pipes. Samples of the mains water supply were taken and 19 of the 20 samples were found to have long and short asbestos fibers, with an average concentration of 0.9 and 6.2 million fibers per liter, respectively.…”
Section: Asbestos In Water According To the Source Of Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Christchurch, New Zealand [ 64 ], reported on the presence of asbestos fibers in the drinking water supply due to aging asbestos-cement pipes. Samples of the mains water supply were taken and 19 of the 20 samples were found to have long and short asbestos fibers, with an average concentration of 0.9 and 6.2 million fibers per liter, respectively.…”
Section: Asbestos In Water According To the Source Of Exposurementioning
confidence: 99%
“… 1988 [ 57 ] Christchurch, New Zealand Drinking water TEM 20 0,9 - 6,2 MFL Sampling focused on pipes from the 1930s to the 1960s and there was abundant evidence of fibers released from pipes of this age. 2020 [ 64 ] Canada Drinking water TEM >10 MFL Samples of raw treated and distributed tap water were collected in 71 municipalities in Canada. Coagulation/filtration treatment was found to be effective for the removal of asbestos fibers.…”
Section: Asbestos In Water According To the Source Of Exposurementioning
confidence: 99%
“…To this day, AC pipes are still in use for fresh water supply [74]. Mager et al (2022) report the presence of asbestos fiber in drinking water originating from aging AC pipes in New Zeeland [75]. The pipe system was installed between 1930 and 1960, and to this date, was still releasing asbestos fibers: 10 µm long, with an average concentration of 0.9 million fibers per liter (MFL) and short asbestos fibers (0.5 µm) with an average concentration of 6.2 MFL.…”
Section: Cementmentioning
confidence: 99%
“…Despite the number of studies linking gastrointestinal cancer with constant ingestion of asbestos, Canada, USA, New Zeeland, and Australia do not ban the use of asbestos-containing pipes. There are large DWDS containing asbestos that are slowly replaced [74,75,[98][99][100][101]].…”
Section: Cementmentioning
confidence: 99%